2015
DOI: 10.1002/14651858.cd011546.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for cognitive decline in people with Down syndrome

Abstract: Due to the low quality of the body of evidence in this review, it is difficult to draw conclusions about the effectiveness of any pharmacological intervention for cognitive decline in people with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 70 publications
0
27
0
1
Order By: Relevance
“…A 2015 Cochrane review of medication for dementia in people with Down syndrome (Livingstone, Hanratty, McShane, & Macdonald, 2015) concluded that overall, the quality of evidence is low which prevents firm conclusions to be made and the authors argued for further trials. However, it is probably unlikely to conduct trials based on withholding treatments (in a placebo arm) from individuals with dementia if those treatments are accepted practice and recommended by current guidance.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…A 2015 Cochrane review of medication for dementia in people with Down syndrome (Livingstone, Hanratty, McShane, & Macdonald, 2015) concluded that overall, the quality of evidence is low which prevents firm conclusions to be made and the authors argued for further trials. However, it is probably unlikely to conduct trials based on withholding treatments (in a placebo arm) from individuals with dementia if those treatments are accepted practice and recommended by current guidance.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Furthermore, it would enable specific therapeutic interventions. Currently, treatment options are limited: in the few randomized controlled trials in the DS population, effectiveness of donepezil and memantine was not proven [13]. Alternatively, contemporary intellectual disability care focuses on timely (non-)pharmacologic therapy to reduce behavioral and psychological symptoms of dementia—the major cause of referral [14]—to improve quality of life and reduce caregiver burden [10], [15].…”
Section: Introduction: Down Syndrome At High Risk For Alzheimer's Dismentioning
confidence: 99%
“…Dessa forma, novas abordagens são necessárias (BALLARD et al, 2016). Ainda existem poucos estudos experimentais controlados e desenhados de forma adequada nesta área (LIVINGSTONE et al, 2015). Assim, novas pesquisas que avaliem estratégias nutricionais potencialmente capazes de amenizar os sintomas relacionados ao Alzheimer e à prevenção da demência relacionadas à SD fazem-se necessárias.…”
Section: Discussionunclassified